The preference level and chemical characteristic of vanamei shrimp otak-otak with the addition of carrageenan - Saffanah, Kayla Zahira; Liviawaty, Evi; Rostika, Rita; Pratama, Rusky Intan (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Carrageenan is a polysaccharide extracted from the seaweed, Kappaphycus alvarezii. Carrageenan serves as a food additive, functioning as both a stabilizer and a gelling agent in vanamei shrimp otak-otak (a type of Indonesian fish cake). This study aimed to determine the effect of different carrageenan concentrations on the sensory acceptance and chemical characteristics of the vannamei shrimp otak-otak. The study was conducted using an experimental method with five treatments: carrageenan addition of 0% (A), 0,5% (B), 1% (C), 1,5% (D), and 2% (E). Preference was assessed using a hedonic test covering appearance, aroma, texture, and taste, as well as a chemical test measuring moisture, ash, fat, protein, carbohydrate, and crude fiber content. Based on the analysis of 20 semi-trained panelists, the most preferred treatment was the addition of 1% carrageenan, with average scores of 7.4 (liked) for appearance, 7.1 (liked) for aroma, 7.5 (liked) for texture, and 7.3 (liked) for taste. Chemical analysis showed 54.66% moisture, 2.34% ash, 8.08% protein, 0.01% fat, 34.91% carbohydrate, and 2.72% crude fiber. The addition of 1% carrageenan was identified as the most favorable concentration compared with the other treatments.